An Obscure Case of Hepatic Subcapsular Hematoma - Albert Ndzengue; Fadi Hammoudeh; Pierre Brutus; Ofem Ajah; Roland Purcell; Joseph Leadon; Richard B. Rafal; Simon Balmir; Danilo A. Enriquez; Gerald L. Posner; Eric A. Jaffe; Pradeep Chandra (Case Reports in Gastroenterology, 2011)
Spontaneous liver bleeding is often reported in preeclampsia. It is otherwise rare and has been linked to gross anatomical lesions and coagulopathy. We report a case of subcapsular hematoma of the liver without any apparent lesion and in the absence of coagulopathy. A 41-year-old male, paraplegic for 16 years, presented to the emergency department 3 days after sudden onset of right upper quadrant and shoulder pain. He had been on vitamins and 5,000 units subcutaneous heparin 12-hourly at the nursing home for the last month. He was in no distress, afebrile, with stable vitals. Physical examination showed a diverting colostomy, tender hepatomegaly and sacral decubiti. A fecal occult blood test was negative. There was spastic paraplegia below the level of T12. Two days after admission, the patient was afebrile and hemodynamically stable. PTT, PT, liver profile, BUN and creatinine were all normal, however his hemoglobin had dropped from 11.3 to 7.6 g/dl. An abdominal CT scan revealed an isolated 9.0 × 1.8 cm subcapsular hematoma. The patient received blood transfusion in the intensive care unit and was discharged 7 days later. In conclusion, spontaneous liver hemorrhage occurs in the nonobstetrical population in the setting of gross anatomical lesions or coagulopathy. This is the first report of an isolated subcapsular liver hematoma.